Phytoplanktonic Photoacclimation Under Clouds - Charlotte Begouen Demeaux; Emmanuel Boss; Jason R. Graff; Michael J. Behrenfeld; Toby K. Westberry (Geophysical Research Letters)
Abstract Phytoplankton photoacclimation is a well‐documented response to changes in light and nutrient availability, with the Chlorophyll a to phytoplankton Carbon ratio (θ = Chl: Cphyto) increasing at low light and decreasing under high light to optimize growth rate. Accurate estimation of phytoplankton growth rates and Net Primary Production (NPP) from space requires knowledge of θ, but cloud cover creates gaps. Current NPP models fill in the gaps by interpolating Chl (and other inputs) from clear‐sky pixels, ignoring the possibility of photoacclimation underneath clouds. Using data from ≈9,000 matchups between BioGeoChemical‐Argo floats and cloud cover from the Moderate Resolution Imaging Spectroradiometer, we compared the response of θ to irradiances under cloudy and clear skies. We found that phytoplankton photoacclimate similarly regardless of sky conditions at the global scale. This study highlights an incorrect assumption in current NPP estimates and suggests ways to improve global assessments of both chlorophyll and NPP.